Estrategias educativas de afrontamiento al acoso escolar en los estudiantes de sexto grado paralelo “c” de la escuela de educación básica 18 de noviembre de la ciudad de Loja, periodo académico 2018-2019. - Ojeda Camacho, Fatima Morayma (2019)
The present investigative work denominated: EDUCATIONAL STRATEGIES OF COPING TO SCHOOL HARASSMENT IN THE STUDENTS OF SIXTH GRADE PARALLEL "C" OF THE BASIC EDUCATION SCHOOL NOVEMBER 18 OF THE CITY OF LOJA, ACADEMIC PERISHED 2018-2019, Its general objective was to implement educational strategies to deal with bullying in students. The research carried out was descriptive, cross-sectional and pre-experimental design; the methods applied were: scientific, analytical-synthetic, deductive, inductive all these methods fulfilled specific roles during the research process. The Cisneros Self Test is used as an instrument to identify the global index as well as the intensity of school bullying, as well as the characteristics of the same. The sample under study corresponds to 32 students. The results of the Pre-test considering the highest levels were: Global index of harassment (56% high), intensity (50% high), scales: contempt-ridicule (56% high), coercion (63% high), restriction- communication (63% high), aggression (50% high), intimidation (50% high), social-exclusion block (53% high) and verbal harassment (47% high). After the application of the proposal, the levels of the scales decreased significantly, placing the highest percentages in the low levels as results of the Post-test: Global index of harassment (63% low), intensity (56% low), scales contempt-ridicule (66% low), coercion (66% low), restriction-communication (78% low), aggression (63% low), intimidation (69% low), social-exclusion block (53% low) and verbal harassment (59 %low). The effectiveness of the implementation of the educational strategies of coping strategies was 89.6% according to the validation of the workshops with a positive impact on the students. It is concluded that students lowered the level of bullying through the use of different educational coping strategies. Therefore it is important that the educational institution of continuity with the application of the workshops to the entire school, including parents and teachers together to address this problem, to improve the school coexistence of each student.